Umeclidinium in chronic obstructive pulmonary disease: latest evidence and place in therapy - Babu, Kesavan Suresh (Ther Adv Chronic Dis, 2017)
Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity, mortality and health care expenditure throughout the world. COPD guidelines recommend the use of long-acting muscarinic antagonist (LAMA) either alone or in combination with a long-acting β(2) agonist (LABA). For over 10 years, tiotropium was the only LAMA that was used in the management of COPD. Over the past few years, various new drugs have been identified that act on the muscarinic receptors and β(2) receptors. Umeclidinium (Umec) is a new LAMA currently approved for use in patients with COPD either as monotherapy or in combination with vilanterol (Vil). Both Umec alone and in combination with Vil delivered through a multi-dose dry powder Ellipta™ device have shown improvement in lung function, health-related quality of life and exacerbation frequency in patients with COPD. This review provides an overview of the pharmacology, pharmacodynamics and pharmacokinetics of Umec, and evaluates the clinical efficacy and safety studies in patients with COPD.